The Effect of Pregnant Women’s Participation in Pregnancy Classes about Breastfeeding Skills: A Quasi-Experimental Study - Yusniarita, Yusniarita; Purnama Eka Sari, Wenny Indah (Fakultas Ilmu-ilmu Kesehatan, 2023)
Pregnant women can benefit from exclusive breastfeeding. Therefore, to raise awareness of exclusive breastfeeding and hone their breastfeeding skills, mothers can participate in pregnancy classes. This study aimed to determine the effect of pregnant women’s participation in pregnancy classes on their breastfeeding skills. This is a quasi-experimental study with a control group and a double post-test design. The samples were selected by using random permuted block sampling. The sample size that met the inclusion criteria was 80 pregnant women in their third trimester domiciled in the work area of ​​the Perumnas and Curup Public Health Center. The intervention group was given pregnant women classes with the Breastfeeding Preparation Module. This study used checklists to assess the respondent’s breastfeeding skills. The data obtained were analyzed using the dependent T-test. The results showed that pregnant women's participation in pregnancy classes affected their breastfeeding skills (p-value < 0.05). Pregnancy classes regarding exclusive breastfeeding are recommended for pregnant women to succeed at breastfeeding, especially exclusive breastfeeding